2018
DOI: 10.1074/jbc.ra118.001978
|View full text |Cite
|
Sign up to set email alerts
|

TAILS N-terminomics and proteomics reveal complex regulation of proteolytic cleavage by O-glycosylation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 80 publications
3
28
0
1
Order By: Relevance
“…We previously developed techniques that allow the identification of site‐specific O‐glycosylation on a proteome‐wide basis, which has enabled high‐throughput mapping of sites of O‐glycan attachment in proteomes from both cell lines and tissues . Furthermore, we have shown that targeted KO of individual GALNT s allows for discovery of GalNAc‐T isoform‐specific substrates . Two approaches were used to characterize the differential O‐glycoproteomes of ΔT1, ΔT2, and ΔT3.…”
Section: Resultsmentioning
confidence: 99%
“…We previously developed techniques that allow the identification of site‐specific O‐glycosylation on a proteome‐wide basis, which has enabled high‐throughput mapping of sites of O‐glycan attachment in proteomes from both cell lines and tissues . Furthermore, we have shown that targeted KO of individual GALNT s allows for discovery of GalNAc‐T isoform‐specific substrates . Two approaches were used to characterize the differential O‐glycoproteomes of ΔT1, ΔT2, and ΔT3.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past 10 years numerous studies have highlighted how various PTMs impact eukaryote biology. In eukaryotes, protease activity plays a critical role in homeostasis and health by maintaining strict control over protein and cellular function [37][38][39][40] . In prokaryote biology, however, systems analysis of proteolysis is in its infancy 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned glycoproteomics studies performed on glycoprotein samples from unaltered biological sources, the SimpleCell technology, which manipulates cells to homogenously express truncated O -GalNAc glycans (Tn and sialyl-Tn (sTn)) on mucins and mucin-like domains due to the inactivation of the chaperone COSMC , represents an important innovation relevant for glycoproteomics [ 84–88 ]. The SimpleCell technology has not only opened exciting avenues to study the challenging mucin glycobiology including how O -glycans impact proteolytic cleavage events, the substrate-specificity of GalNAc-transferases and the role of O -GalNAc glycans in cell–cell interactions and cell differentiation [ 89–93 ], but has also improved our ability to profile the critically underexplored O -glycoproteome. Glycoproteomics efforts using the SimpleCell technology to study mucin-type glycosylation in different human and other mammalian cell lines have led to an impressive database ( http://www.glycoproteomics.somee.com/ ), comprising a total of 18 397 unique O -glycopeptides spanning 10 197 O -glycan sites from 2039 O -glycoproteins within the human O -glycoproteome supported by glycopeptide MS/MS evidence.…”
Section: Recent N - and O -Glycmentioning
confidence: 99%